Winning = meriah keberhasilan Jack Welch bersama Suzy Welch ; alih bahasa, Alexznder Sindoro ; editor, Lundon Saputra, Sigit Suryanto - WELCH, Jack; Welch, Suzy; Sindoro, Alexander; saputra, Lyndon; Suryanto, Sigit (2006)
359 hlm 24 cm